Odpowiedzi

2010-03-08T17:20:33+01:00
A) 2(x+3)=10
2x+6=10
2x=10-6 |:2
x=2
b) 3(x-1)+2=8
3x-3+2=8
3x=8+3-2 |:3
x=3
c)3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x=-9+8+1
x=0
d)3x+11=41
3x=41-11 |:3x
x=10
e)½x+3=7
½x=7-3 |*2
x=8
f)7(x+3)=5x+2+2x
7x+21=5x+2+2x
7x-5x-2x=-21+2
0x=-19
Najlepsza Odpowiedź!
2010-03-08T17:21:00+01:00
2(x+3)=10
2x+6=10
2x=10/-6
2x=4/:2
x=2

b. 3(x-1)+2=8
3x-3+2=8
3x=8+3-2
3x=9/:3
x=3

c. 3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=8+1-9
-x=0/:(-1)
x=0

d. 3x+11=41
3x=41-11
3x=30/:3
x=10


e. ½x+3=7 /*2
x+6=14
x=14-6
x=8

f. 7(x+3)=5x+2+2x
7x+21=5x+2+2x
7x-5x-2x=-21+2
-x=-19/:(-1)
x=19

2010-03-08T17:31:15+01:00
A) 2x+6=10
2x=10-6
2x=4 /:2
x=2
b) 3x-3+2=8
3x=8+3-2
3x= 9/:3
x=3
c)3x+9=2x+8+x+1
3x-2x-x= 8+1
-x=9 /:(-1)
x=-9

d)3x=41-11
3x=30/:3
x=10

e)½x= 7-3
½x=4/:½
x= 2

f) 7x+21=5x+2+2x
7x-5x-2x=-21+2
0=-19